Capped high-force integrin bond lifetimes and spacing-tuned binding frequency drive rapid fibroblast migration - Jingjing Feng; Keshu Feng; Zhaohui Xiong; Miao Yu; Yuru Hu; Wenxu Wang; Ruihao Xue; Ze Gong; Zheng Liu; Wei Chen (Proceedings of the National Academy of Sciences, 2025)
Cell migration relies on balancing focal adhesion (FA) stability—necessary for traction generation—and turnover—essential for forward translocation. Here, we dissect how integrin binding frequency and force-dependent bond duration jointly regulate this balance in fibroblasts. Using block copolymer micelle nanolithography, we create gold nanoparticle (Au NP) arrays with controlled spacings to vary integrin–ligand binding frequency. In parallel, tension gauge tethers (TGTs) with defined force threshold limit bond lifetime of high-force integrins under cellular traction. We find that intermediate ligand spacing coupled with a moderate rupture threshold dramatically accelerates fibroblast migration—up to twelvefold faster than on denser or sparser substrates. These conditions foster rapid FA turnover and support a dendritic actin architecture driven by lamellipodia, challenging the longstanding view of fibroblasts as inherently slow, mesenchymal movers. Knockout and blocking experiments further identify α5β1 as the mechanically dominant integrin subtype that plays a pivotal role in supporting this rapid migration. Mechanistically, FAs remain sufficiently stable to generate traction but also disassemble quickly, fostering continuous protrusion–retraction cycles essential for high-speed migration. These findings refine the classic biphasic model of cell migration into a two-dimensional framework that considers ligand spacing (binding frequency) and TGT force thresholds (binding duration). Beyond expanding fundamental understanding of integrin mechanobiology, our results provide broad avenues for tissue engineering and therapeutic applications, where finely tuned adhesion mechanics can markedly modulate cell speed and phenotype.